Effect of exercise on brain-derived neurotrophic factors in middle-aged and older adults with type 2 diabetes mellitus: a systematic review and meta-analysis - Li, Zhihua; Cui, Zhibo; Wang, Tong; Zheng, Haoyu; Li, Kaixing; Yang, Chengbo (Frontiers in Physiology, 2025)
BackgroundAlthough previous studies have indicated that exercise can improve brain-derived neurotrophic factor (BDNF) levels in middle-aged and older adults with type 2 diabetes mellitus (T2DM), discrepancies remain among the findings. Therefore, this study aims to determine the impact of exercise on BDNF concentrations in middle-aged and older adults with T2DM.MethodsA systematic search was conducted across multiple databases, including PubMed, Embase, EBSCO, Cochrane Library, CNKI, and Web of Science, covering the period from the inception of each database to October 2024. The search process adhered to the PRISMA and PERSiST guidelines. Two independent evaluators were responsible for conducting the search, screening results, extracting data, and assessing study quality. A random-effects model was employed to calculate the standardized mean difference (SMD) and 95% confidence interval (CI).ResultsThis meta-analysis included 13 studies involving 206 middle-aged and elderly individuals with T2DM. The results showed that exercise effectively increased BDNF levels in middle-aged and elderly individuals with T2DM (SMD = 0.73, 95% CI: 0.07–1.39, p< 0.001). Subgroup analysis revealed that aerobic exercise and combined exercise did not significantly increase BDNF levels. Chronic exercise (SMD = 1.04, 95% CI: 0.09 to 1.98, p= 0.03) and weekly exercise duration exceeding 150 min (SMD = 1.56, 95% CI: 0.35 to 2.77, p= 0.01) significantly increased BDNF levels in middle-aged and older adults with T2DM. In terms of detection methods, non-instant blood sampling (SMD = 1.27, 95% CI: 0.24 to 2.31, p= 0.02) and serum BDNF testing (SMD = 0.94, 95% CI: 0.22 to 1.66, p= 0.01) were associated with significant increases in BDNF concentrations. There was no significant difference in the effect of diabetes duration ≥10 years versus<10 years on BDNF levels in middle-aged and older adults with T2DM.ConclusionExercise has a significant positive effect on BDNF levels in middle-aged and older adults with T2DM. Chronic exercise and exercise lasting more than 150 min per week have a more significant effect on increasing BDNF levels in middle-aged and older adults with T2DM. In addition, when non-immediate blood sampling methods are used to measure serum BDNF levels after exercise, a significant increase in BDNF concentration is observed.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/#myprospero, identifier CRD42024621098.